How Customers Evaluate Genitalia versus Torso Sex Toys on Amazon.com: A Content Analysis of Product Reviews - Nicola Döring; Veronika Mikhailova; Pari-Gole Noorishad (MDPI AG, 2022)
Sex toys are widely marketed on the Internet. Browsing for, buying, and reviewing sex toys online are popular cybersexual activities. The aim of this study was to investigate consumers' experiences with different types of realistic sex toys via online product reviews on Amazon.com. Toys were categorized in a 2 × 2 design regarding their representation of the human body (genitalia sex toys representing reproductive organs only versus torso toys representing larger parts of the human body) and their depiction of gender (toys representing female versus male body parts). Informed by feminist discourses on sex toys as well as sexual script theory and consumer research, the study explored the overall evaluations (RQ1), most frequently addressed characteristics (RQ2), usage patterns (RQ3), and perceived effects (RQ4) of the four groups of sex toys. A quantitative manual content analysis of N = 778 online sex toy reviews showed that 79% of consumers gave popular realistic sex toys positive ratings (RQ1). The most frequently mentioned characteristics were quality, material, and shape (RQ2). Most reviewers were men and used sex toys for solo sexual activities (RQ3). An additional qualitative analysis of n = 69 reviews addressing the perceived effects of sex toy use revealed that consumers predominantly mentioned positive effects (RQ4). Genitalia sex toys received better evaluations than torso sex toys and were perceived to be complementary tools to enhance sexual arousal, whereas the use of torso toys entailed anthropomorphization and symbolic social interactions. Implications for future research and design of different types of sex toys are discussed.